Effect of Acupuncture on MMP-2/9 and VEGF Expression in Intracerebral Hemorrhage Model Rats - Xinyi HUANG; Zhuolin YANG; Qiulei MA; Qingzhang ZHOU; Xiaozhuo SUN (康复学报)
Objective:To observe the effect of acupuncture at different time points on the expression of matrix metalloproteinase-2/9 (MMP-2/9) and vascular endothelial growth factor (VEGF) in rats at acupoints Neiguan and Shuigou, so as to explore the mechanism of acupuncture on angiogenesis and neural protection.Methods:A total of 135 male Wistar rats were randomly divided into mock surgical group, model 3 h group, model 9 h group, model 24 h group, model 48 h group, 3 h acupuncture group, 9 h acupuncture group, 24 h acupuncture group, 48 h acupuncture group, with 15 animals in each group; the ICH model was made by the caudate nucleus autologous slow blood injection method and the MMP-2/9 and VEGF positive cell counts were detected by immunohistochemistry.Results:The blood-brain barrier MMP-2,MMP-9 and VEGF positive cells in the 3,9,24,48 h acupuncture groups were significantly lower than those of model group at the same time, compared with the 9,24,48 h acupuncture groups, the reduction of MMP-2 and MMP-9 positive cells was more obvious in the 3 h acupuncture group. The VEGF-positive cells in the blood-brain barrier of 3,9 h acupuncture groups were significantly lower than the model group at the same time point, but, VEGF-positive cells of 24,48 h acupuncture groups was significantly more than the model group at the same time point, with statistically significant differences (P<0.05).Conclusion:Acupuncture Neiguan and Shuigou at different time points can inhibit the expression of MMP-2/9 positive cells of rats with intracerebral hemorrhage and increase the expression of VEGF positive cells, and the earlier the acupuncture time after cerebral hemorrhage, the more can it promote angiogenesis and nerve regeneration, to protect the brain's nervous system.